Polymeric nitrogen material and synthesis method thereof

By dissolving the azide precursor in a liquid in a low vacuum environment and heating, insulation and cooling, the problem of high pressure and extreme conditions required for synthesis of polymerized nitrogen materials in the prior art is solved, and the possibility of synthesizing high-level polymerized nitrogen materials under normal pressure is realized, and the material is stable at normal temperature and normal pressure.

CN119706756APending Publication Date: 2025-03-28INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411381606.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The method of synthesizing polymeric nitrogen materials in the prior art requires high pressure and extreme conditions, and the synthetic materials cannot exist stably under normal pressure and have a low content.

Method used

The polymerized nitrogen material is synthesized by dissolving the azide precursor in a liquid and heating, insulation and cooling in a low vacuum environment. This method promotes the decomposition and reaction of precursors by adding liquid, reducing the pressure required for synthesis.

Benefits of technology

The possibility of synthesizing polymeric nitrogen materials under normal pressure is realized, the yield of the material is improved, and the synthesis process is simpler and easier, and the material can exist stably under normal temperature and pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706756A_ABST
    Figure CN119706756A_ABST
Patent Text Reader

Abstract

The invention discloses a polymeric nitrogen material and a synthesis method thereof, belongs to the technical field of energetic materials, and is used for solving one of the following technical problems: (1) a method for synthesizing a polymeric nitrogen material in the prior art is relatively high in required pressure intensity, harsh in condition and difficult to implement; (2) the polymerized nitrogen material synthesized in the prior art cannot stably exist under normal pressure; and (3) the content of the polymerized nitrogen material synthesized in the prior art is low. The synthesis method comprises the following steps: dissolving an azide precursor in a solution to obtain a mixed solution, and carrying out heating, heat preservation and cooling on the mixed solution in a low vacuum environment to obtain the polymeric nitrogen material. The synthesis method provided by the invention can reduce the synthesis pressure to obtain the polymeric nitrogen material, the method is simple, and the yield of the polymeric nitrogen material is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energetic materials, and in particular relates to a polymeric nitrogen material and a synthesis method thereof. Background Art

[0002] In the field of energy and materials, people have been committed to finding materials with high energy density. The energy density of traditional energetic materials has gradually approached its theoretical limit and it is difficult to meet the increasingly tense military needs. Nitrogen has the potential to form high energy density materials due to its unique electronic structure. The bond energy of the N≡N triple bond is 954kJ / mol, which is one of the strongest chemical bonds, and the bond energy of the NN single bond is 160kJ / mol. The polymerized nitrogen (hereinafter referred to as cg-PN) material formed by the NN single bond releases huge energy when it decomposes into gaseous N≡N triple bond nitrogen, and its energy release capacity far exceeds that of traditional energetic materials. Due to its high energy density and the decomposition product of nitrogen, polymerized cg-PN materials are expected to play an important role in practical applications.

[0003] At present, the synthesis of cg-PN usually needs to be prepared under extreme conditions such as high temperature and high pressure. In 2004, Eremets et al. reported the successful synthesis of cg-PN using molecular nitrogen as a precursor, at a pressure of about 110 GPa and a temperature of 2000 K. Unfortunately, cg-PN cannot exist stably under normal pressure.

[0004] In recent years, cg-PN has been studied in detail in theory, but experimental studies have rarely been reported. Extreme conditions of high temperature and high pressure make it difficult to support the scale-up production of cg-PN. How to obtain cg-PN with a higher content under normal pressure remains an urgent problem to be solved. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a polymeric nitrogen material and a method for synthesizing the same, so as to solve one of the following technical problems: (1) The method for synthesizing the polymeric nitrogen material in the prior art requires a high pressure and harsh conditions, which are not easy to achieve; (2) The polymeric nitrogen material synthesized in the prior art cannot exist stably under normal pressure; (3) The content of the polymeric nitrogen material synthesized in the prior art is low.

[0006] The purpose of the present invention is mainly achieved through the following technical solutions:

[0007] A method for synthesizing a polymerized nitrogen material comprises: dissolving an azide precursor in a liquid to obtain a mixed liquid, and heating, keeping the mixed liquid warm, and cooling the mixed liquid in a low vacuum environment to obtain the polymerized nitrogen material.

[0008] Further, the azide precursor includes one or more of NH4N3, NaN3, LiN3 and KN3.

[0009] Furthermore, the liquid includes water, alcohol, acid solution or alkaline solution.

[0010] Further, the mass of the liquid is more than 40% of the mass of the azide precursor.

[0011] Furthermore, the mass ratio of the liquid to the azide precursor is 4-5:1-2.

[0012] Furthermore, the vacuum degree of the low vacuum environment is 0-200Pa.

[0013] Further, the mixed solution is heated to 70-330°C.

[0014] Furthermore, when the azide precursor is NH4N3, the insulation temperature is 70-90°C.

[0015] Furthermore, when the azide precursor is LiN3, the holding temperature is 90-105°C.

[0016] The present invention also provides a polymeric nitrogen material, which is prepared by the above-mentioned synthesis method.

[0017] Compared with the prior art, the present invention can achieve at least one of the following technical effects:

[0018] 1) The synthesis method of the polymeric nitrogen material of the present invention promotes the decomposition of the azide precursor and its participation in the reaction by adding a liquid to synthesize the polymeric nitrogen material, breaking through the high pressure condition required for the synthesis of cg-PN in the traditional technology. The synthesis pressure of cg-PN is relatively low, which greatly reduces the difficulty of synthesis and becomes a new method for synthesizing cg-PN.

[0019] 2) The synthesis method of the polymeric nitrogen material of the present invention is simple and easy to implement, which greatly reduces the difficulty of synthesis.

[0020] 3) The yield of cg-PN obtained by the synthesis method of the polymerized nitrogen material of the present invention is higher, and the cg-PN material can maintain its stability at room temperature and pressure, breaking through the limitations of traditional technologies that polymerized cg-PN materials can only exist under high pressure or have low yields. This feature makes the material expected to open up new application prospects in the fields of energy storage, high-density energetic materials, etc.

[0021] Other features and advantages of the present invention will be described in the following description, and part of them may become obvious from the description, or may be understood by practicing the present invention. The purpose and other advantages of the present invention may be realized and obtained by the structures particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference numerals refer to like components throughout the drawings.

[0023] Figure 1 is the Raman spectrum of cg-PN of Example 1 of the present invention;

[0024] Figure 2 is the Raman spectrum of cg-PN of Example 2 of the present invention;

[0025] Figure 3 It is the Raman spectrum of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0026] A polymeric nitrogen material and a synthesis method thereof are further described in detail below in conjunction with specific examples. These examples are only used for comparison and explanation purposes, and the present invention is not limited to these examples.

[0027] The invention provides a method for synthesizing a polymerized nitrogen material, comprising: dissolving an azide precursor in a liquid to obtain a mixed liquid, heating the mixed liquid to a holding temperature, holding the temperature, and cooling the mixed liquid in a low vacuum environment to obtain the polymerized nitrogen material.

[0028] Specifically, the azide precursor includes one or more of NH4N3, NaN3, LiN3 and KN3.

[0029] Specifically, the above-mentioned liquid includes water, alcohol, acid solution or alkaline solution, etc.

[0030] Specifically, the acid solution may be one or more of a hydrochloric acid solution and an acetic acid solution.

[0031] Specifically, the concentration of the acid solution may be 0.01 to 0.1 mol / L.

[0032] Specifically, the alkaline solution may be one or more of a calcium hydroxide solution and a sodium hydroxide solution.

[0033] Specifically, the concentration of the alkaline solution may be 0.1 to 5 mol / L.

[0034] Considering that too much liquid makes it difficult to evacuate, and too little liquid makes the azide precursor insoluble. Therefore, the mass of the liquid is controlled to be more than 40% of the azide precursor. Preferably, the mass ratio of the liquid to the azide precursor is 4-5:1-2.

[0035] Specifically, the vacuum degree of the low vacuum environment is 0 to 200 Pa, for example, 10 Pa, 20 Pa, 30 Pa, 40 Pa, 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa, 120 Pa, 140 Pa, 160 Pa, 180 Pa, and 200 Pa.

[0036] Specifically, the mixed solution is heated to 70-330° C., kept at this temperature for 3-24 hours, and cooled to obtain the polymerized nitrogen material.

[0037] Specifically, when the azide precursor is NH4N3, the holding temperature is 70-90°C, for example, 75°C, 80°C, or 85°C.

[0038] Specifically, when the azide precursor is LiN3, the holding temperature is 90-105°C, for example, 95°C, 100°C, or 105°C.

[0039] Specifically, when the azide precursor is NaN3, the holding temperature is 200-280°C, for example, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C.

[0040] Specifically, when the azide precursor is KN3, the holding temperature is 250-330°C, for example, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C.

[0041] Considering that too high a heating rate will lead to uneven heating of the raw materials, and too low a heating rate will lead to insufficient sintering and prolonged sintering time. Therefore, the heating rate is controlled to be 2-10°C / min. For example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min.

[0042] Specifically, the above synthesis method comprises the following steps:

[0043] S1, placing an azide precursor and a liquid in a container and dissolving them to obtain a mixed solution;

[0044] S2, placing the mixed solution in a container (e.g., on a glass sheet, a quartz boat, or a crucible), and then placing it in a tube furnace and evacuating the tube furnace;

[0045] S3, subjecting the sample in the tube furnace to vacuum or flowing gas protection, heating it to the insulation temperature and performing insulation operation;

[0046] S4. Cooling the tubular furnace to synthesize cg-PN.

[0047] Specifically, in the above S1, the container can be a glass beaker or a glass weighing bottle, etc.

[0048] Specifically, in the above S2, the number of vacuuming can be 1 to 4 times. The vacuum degree after the vacuuming treatment is 0 to 200 Pa, for example, 10 Pa, 20 Pa, 30 Pa, 40 Pa, 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa, 120 Pa, 140 Pa, 160 Pa, 180 Pa, 200 Pa.

[0049] Specifically, in the above S3, the vacuum degree of the vacuum is 1-5Pa, for example, 2Pa, 3Pa, 4Pa, 5Pa.

[0050] Specifically, in the above S3, the gas includes oxygen, hydrogen, nitrogen, argon or helium, etc., and one or more gases can be introduced.

[0051] Considering that in S3, too high a gas flow rate will lead to too high a pressure in the tube furnace, which is not conducive to the synthesis of cg-PN. Therefore, the gas flow rate is controlled to be 1 to 50 standard cubic centimeters. For example, 10 standard cubic centimeters, 20 standard cubic centimeters, 30 standard cubic centimeters, and 40 standard cubic centimeters.

[0052] Specifically, in the above S3, the heating rate is set to 2 to 10°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min; the insulation time is 3 to 24h, for example, 4h, 5h, 7h, 10h, 12h, 15h, 18h, 20h, 22h.

[0053] Specifically, in the above S4, a rapid cooling method is generally adopted, and the cooling rate is 50 to 200°C / min, for example, 50°C / min, 100°C / min, 150°C / min, 200°C / min.

[0054] The present invention also provides a polymeric nitrogen material, which is synthesized by the above-mentioned synthesis method.

[0055] The polymeric nitrogen material of the present invention is formed by a NN single bond, and when decomposed into an N≡N triple bond, it releases huge energy, and its energy release capacity far exceeds that of traditional energetic materials.

[0056] In the Raman spectrum of the polymerized nitrogen (cg-PN) of the present invention, 634 cm -1 The Raman peak corresponding to the A mode of cg-PN indicates that the polymerized nitrogen (cg-PN) of the present invention has the following structural characteristics:

[0057] 1) Basic structural unit

[0058] A polymer formed by nitrogen atoms connected to each other by single bonds (N—N). The single bonds between nitrogen atoms have lower bond energy than the strong triple bonds (N≡N) in nitrogen molecules, but this structural change allows polymerized nitrogen to release a large amount of energy when it decomposes into nitrogen gas.

[0059] 2) Spatial configuration

[0060] It has a cubic deflection structure, which has a certain spatial distortion. This cubic deflection structure makes the arrangement of nitrogen atoms have a unique spatial orientation and symmetry.

[0061] The polymeric nitrogen material of the present invention introduces H ions during the solubilization process by adding liquid, which can saturate the dangling bonds on the surface of cg-PN, so that cg-PN can exist stably at room temperature and pressure.

[0062] In the synthesis method of the present invention, by adding liquid, the decomposition of the azide precursor is promoted to participate in the reaction, thereby reducing the pressure required for the synthesis of cg-PN. Compared with the reaction of synthesizing cg-PN at high temperature and high pressure, the synthesis pressure of cg-PN is lower, which greatly reduces the difficulty of synthesis and becomes a new method for synthesizing cg-PN.

[0063] Specifically, the cg-PN of the present invention is formed by a NN single bond, and when it is decomposed into N≡N triple bond nitrogen, it releases huge energy, and its energy release capacity far exceeds that of traditional energetic materials. At the same time, due to its high energy density and the decomposition product being nitrogen, it is expected to play an important role in practical applications.

[0064] After in-depth research, the inventors explored a new synthesis method to reduce the pressure required for the cg-PN synthesis process, so that cg-PN can be obtained under normal pressure and can exist stably at normal temperature and pressure.

[0065] The yield of cg-PN obtained by the synthesis method of the polymerized nitrogen material of the present invention is higher. For example, in the Raman spectrum, the intensity of the Raman peak corresponding to the A mode of cg-PN is above 18900, for example, 18926-20803, which is more than 0.9 times the characteristic peak of the raw material, for example, 0.95-3 times. In addition, the cg-PN material of the present invention can maintain its stability at room temperature and pressure, breaking through the limitation that the polymerized cg-PN material in the traditional technology can only exist under high pressure. This feature makes the material promising to open up new application prospects in the fields of energy storage, high energy density energetic materials, etc.

[0066] The embodiments and comparative examples of the present invention use a ReniShaw Raman spectrometer to measure Raman spectra, with a laser wavelength of 532 nm, a grating of 2400 l / mm, a power output of 0.5% to 5% (for example, 0.5%, 1% or 5%), an integration time of 10 to 120 s (for example, 10 s, 30 s, 60 or 120 s), an integration number of 1 to 4 times (for example, 1 time, 2 times, 3 times or 4 times), and a Raman spectrum test range of 100 to 1500 cm -1 .

[0067] Example 1

[0068] This embodiment provides a polymeric nitrogen material and a synthesis method thereof, the synthesis method comprising:

[0069] S1. weighing azide precursor and liquid;

[0070] S2, placing the weighed raw materials in a container for dissolving;

[0071] S3, dropping the above liquid on a glass sheet, then placing the glass sheet in a tube furnace and evacuating the tube furnace;

[0072] S4, performing operations such as flowing gas protection, heating and heat preservation on the samples in the above-mentioned tube furnace;

[0073] S5. Cooling the tubular furnace to synthesize cg-PN.

[0074] Specifically, in the above S1, the azide precursor is KN3, and the mass of KN3 is 100 mg.

[0075] Specifically, in the above S1, the liquid is water, and the mass of the water is 500 mg.

[0076] Specifically, in the above S2, the container is a glass weighing bottle.

[0077] Specifically, in the above S3, the number of vacuuming is 3 times, and the vacuum degree after vacuum treatment is 20Pa.

[0078] Specifically, in the above S4, nitrogen and argon are introduced simultaneously, and the gas flow rates are 15 standard cubic centimeters respectively.

[0079] Specifically, in the above S4, the insulation temperature is 300°C.

[0080] Specifically, in the above S4, the heating rate of the tube furnace is set to 4°C / min, and the tube furnace keeps the sample warm for 3 hours.

[0081] Specifically, in the above S5, the cooling rate is 50°C / min.

[0082] The Raman spectrum of the cg-PN material synthesized in this example is shown in Figure 1 As shown in the Raman spectrum, at 142cm -1 、634cm -1 、1268cm -1 and 1340cm -1 There are 4 obvious strong peaks. - The vibration lattice mode, bending v2 mode and symmetric stretching v1 mode correspond to 142 cm -1 、1268cm -1 and 1340cm -1 , and 634cm -1 The intensity of the Raman peak corresponding to the A mode of cg-PN is 20803, which is about 1.361 times that of the characteristic peak of the raw material, indicating that the polymerized cg-PN material was synthesized using this method.

[0083] Example 2

[0084] This embodiment provides a polymeric nitrogen material and a synthesis method thereof, the synthesis method comprising:

[0085] S1. weighing azide precursor and liquid;

[0086] S2, placing the weighed raw materials in a container and dissolving them to obtain a mixed solution;

[0087] S3, dropping the mixed liquid into a quartz boat, then placing the boat in a tube furnace and evacuating the tube furnace;

[0088] S4, subjecting the sample in the tube furnace to flowing gas protection, heating and heat preservation operations;

[0089] S5. Cooling the tubular furnace to synthesize cg-PN.

[0090] Specifically, in the above S1, the azide precursor is selected as NaN3, and the mass of NaN3 is 200 mg.

[0091] Specifically, in the above S1, the liquid is water, and the mass of the water is 500 mg.

[0092] Specifically, in the above S2, the container is a glass weighing bottle.

[0093] Specifically, in the above S3, the number of vacuuming is 3 times, and the vacuum degree after vacuum treatment is 20Pa.

[0094] Specifically, in the above S4, nitrogen and argon are introduced simultaneously, and the gas flow rates are 15 standard cubic centimeters respectively.

[0095] Specifically, in the above S4, the insulation temperature is 250°C.

[0096] Specifically, in the above S4, the heating rate of the tube furnace is set to 4°C / min, and the tube furnace keeps the sample warm for 3 hours.

[0097] Specifically, in the above S5, the cooling rate is 50°C / min.

[0098] The Raman spectrum of the cg-PN material synthesized in this example is shown in Figure 2 As shown in the Raman spectrum, at 142cm -1 、634cm -1 、1268cm -1 and 1340cm -1 There are 4 obvious strong peaks. - The vibration lattice mode, bending v2 mode and symmetric stretching v1 mode correspond to 142 cm -1 、1268cm -1 and 1340cm -1 , and 634cm -1 The intensity of the Raman peak corresponding to the A mode of cg-PN is 18926, which is about 0.958 times the characteristic peak of the raw material, indicating that the polymerized cg-PN material was synthesized using this method.

[0099] Example 3

[0100] This embodiment provides a polymeric nitrogen material and a synthesis method thereof, the synthesis method comprising:

[0101] S1. weighing azide precursor and liquid;

[0102] S2, placing the weighed raw materials in a container and dissolving them to obtain a mixed solution;

[0103] S3, dropping the mixed liquid onto a quartz boat, then placing the boat in a tube furnace and evacuating the tube furnace;

[0104] S4, subjecting the sample in the tube furnace to flowing gas protection, heating and heat preservation operations;

[0105] S5. Cooling the tubular furnace to synthesize cg-PN.

[0106] Specifically, in the above S1, the azide precursor is LiN3, and the mass of LiN3 is 200 mg.

[0107] Specifically, in the above S1, the liquid is water, and the mass of the water is 500 mg.

[0108] Specifically, in the above S2, the container is a glass weighing bottle.

[0109] Specifically, in the above S3, the number of vacuuming is 3 times, and the vacuum degree after vacuum treatment is 21Pa.

[0110] Specifically, in the above S4, nitrogen and argon are introduced simultaneously, and the gas flow rates are 15 standard cubic centimeters respectively.

[0111] Specifically, in the above S4, the insulation temperature is 100°C.

[0112] Specifically, in the above S4, the heating rate of the tube furnace is set to 4°C / min, and the tube furnace keeps the sample warm for 3 hours.

[0113] Specifically, in the above S5, the cooling rate is 50°C / min.

[0114] In this example, the polymerized cg-PN material was synthesized by using this method. This example also carried out the same Raman spectrum test as in Example 1, and the results were basically the same. Due to limited space, they are not listed one by one.

[0115] Example 4

[0116] This embodiment provides a polymeric nitrogen material and a synthesis method thereof, the synthesis method comprising:

[0117] S1. weighing azide precursor and liquid;

[0118] S2, placing the weighed raw materials in a container and dissolving them to obtain a mixed solution;

[0119] S3, dropping the mixed liquid into a quartz boat, then placing the boat in a tube furnace and evacuating the tube furnace;

[0120] S4, subjecting the sample in the tube furnace to flowing gas protection, heating and heat preservation operations;

[0121] S5. Cooling the tubular furnace to synthesize cg-PN.

[0122] Specifically, in the above S1, the azide precursor is NH4N3, and the mass of NH4N3 is 200 mg.

[0123] Specifically, in the above S1, the liquid is water, and the mass of the water is 500 mg.

[0124] Specifically, in the above S2, the container is a glass weighing bottle.

[0125] Specifically, in the above S3, the number of vacuuming is 3 times, and the vacuum degree after vacuum treatment is 20Pa.

[0126] Specifically, in the above S4, nitrogen and argon are introduced simultaneously, and the gas flow rates are 15 standard cubic centimeters respectively.

[0127] Specifically, in the above S4, the insulation temperature is 80°C.

[0128] Specifically, in the above S4, the heating rate of the tube furnace is set to 4°C / min, and the tube furnace keeps the sample warm for 3 hours.

[0129] Specifically, in the above S5, the cooling rate is 50°C / min.

[0130] In this example, the polymerized cg-PN material was synthesized by using this method. This example also carried out the same Raman spectrum test as in Example 1, and the results were basically the same. Due to limited space, they are not listed one by one.

[0131] Comparative Example 1

[0132] This comparative example provides a method for synthesizing a polymerized cg-PN material without adding a solution. The steps of this comparative example are substantially the same as those of Example 1 and will not be described in detail herein. The difference is that:

[0133] S1. Weigh the azide precursor KN3, the mass of KN3 is 200 mg, and no liquid needs to be added;

[0134] S2, no need for this step;

[0135] S3. Spread the azide precursor KN3 weighed in S1 evenly in a quartz boat, then place it in a tube furnace and evacuate the tube furnace.

[0136] The Raman spectrum of the product of this comparative example is as follows Figure 3 As shown, the Raman spectrum is at 634cm -1 There is no peak at the position of , indicating that the polymerized cg-PN material cannot be synthesized by this method without adding a solution.

[0137] Comparative Example 2

[0138] This comparative example provides a method for synthesizing a polymerized cg-PN material without adding a solution. The steps of this comparative example are substantially the same as those of Example 2 and will not be described in detail herein.

[0139] S1. Weigh the azide precursor NaN3, the mass of NaN3 is 200 mg, and no liquid needs to be added;

[0140] S2, no need for this step;

[0141] S3. Spread the azide precursor NaN3 weighed in S1 evenly in a quartz boat, then place it in a tube furnace and evacuate the tube furnace.

[0142] This comparative example cannot synthesize polymerized cg-PN material.

[0143] Comparative Example 3

[0144] This comparative example provides a method for synthesizing a polymerized cg-PN material without adding a solution. The steps of this comparative example are substantially the same as those of Example 3 and will not be repeated here.

[0145] S1. Weigh the azide precursor LiN3, the mass of LiN3 is 200 mg, and no liquid needs to be added;

[0146] S2, no need for this step;

[0147] S3. Spread the azide precursor LiN3 weighed in S1 evenly in a quartz boat, then place it in a tube furnace and evacuate the tube furnace.

[0148] This comparative example cannot synthesize polymerized cg-PN material.

[0149] Comparative Example 4

[0150] This comparative example provides a method for synthesizing a polymerized cg-PN material without adding a solution. The steps of this comparative example are substantially the same as those of Example 4 and will not be repeated here.

[0151] S1. Weigh the azide precursor NH4N3, the mass of NH4N3 is 200 mg, and no liquid needs to be added;

[0152] S2, no need for this step;

[0153] S3. Spread the azide precursor NH4N3 weighed in S1 evenly in a quartz boat, then place it in a tube furnace and evacuate the tube furnace.

[0154] This comparative example cannot synthesize polymerized cg-PN material.

[0155] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for synthesizing a polymeric nitrogen material, characterized in that: include: The azide precursor is dissolved in a liquid to obtain a mixed liquid, and the mixed liquid is heated, kept warm, and cooled in a low vacuum environment to obtain a polymerized nitrogen material.

2. The synthesis method according to claim 1, characterized in that The azide precursor includes one or more of NH4N3, NaN3, LiN3 and KN3.

3. The synthesis method according to claim 1, characterized in that The liquid includes water, alcohol, acid solution or alkaline solution.

4. The synthesis method according to claim 1, characterized in that The mass of the liquid is more than 40% of the azide precursor.

5. The synthesis method according to claim 1, characterized in that The mass ratio of the liquid to the azide precursor is 4-5:1-2.

6. The synthesis method according to claim 1, characterized in that The vacuum degree of the low vacuum environment is 0-200Pa.

7. The synthesis method according to claim 1, characterized in that The mixed solution is heated to 70-330°C.

8. The synthesis method according to any one of claims 1 to 7, characterized in that When the azide precursor is NH4N3, the holding temperature is 70-90°C.

9. The synthesis method according to any one of claims 1 to 7, characterized in that When the azide precursor is LiN3, the holding temperature is 90-105°C.

10. A polymeric nitrogen material, characterized in that: The polymeric nitrogen material is prepared by the synthesis method according to any one of claims 1 to 9.